Penyuluhan Pencegahan Dan Penanganan KDRT - Alexander Djuang Papay; Rikardo D. Butar-Butar; Yefta Arisma; Bulu Salempang4 (Sekolah Tinggi Teologi Real Batam, 2018)
Violence in the household is an act that is carried out in the household by a husband, wife, or child, which has a negative impact on physical, psychological integrity and harmonious relationships. There are various forms of violence that occur in households, and it could be that we are experiencing violence without realizing it, or in the households around us. Domestic violence is an act that violates the law because it needs to be prevented. For that, every individual needs to know and understand what domestic violence is, what are the factors for the occurrence of domestic violence and how to overcome it. AbstrakKekerasan dalam rumah tangga merupakan tindakan yang dilakukan didalam rumah tangga baik oleh suami, istri, maupun anak yang memberi dampak buruk bagi keutuhan fisik, psikis dan keharmonisan hubungan. Ada berbagai bentuk kekerasan yang terjadi dalam rumah tangga, dan bisa saja tanpa disadari kekerasan itu sedang kita alami, ataupun rumah tangga disekitar kita. Kekerasan dalam rumah tangga perbuatan yang melanggar hukum karena itu perlu dilakukan pencegahan. Untuk itu setiap individu perlu mengetahui dan memahami apa itu kekerasan dalam rumah tangga, apa yang mejadi faktor-faktor terjadinya kekerasan dalam rumah tangga dan bagaimana menanggulanginya